Do internal capital markets in business groups mitigate firms' financial constraints? - Kabbach-de-Castro, Luiz Ricardo; Kirch, Guilherme; Matta, Rafael (Journal of Banking & Finance, 2022)
We develop a new rationale for capital allocation in business groups’ internal capital markets. We show that productivity and pledgeable income jointly drive capital allocation within an internal capital market. In financially constrained business groups, an efficient internal capital market can allocate marginal funds to firms that have high pledgeability of income because of a multiplier effect: a dollar of internal funds generates a bigger increase in investment. This result has important implications for the business group affiliation strategy. Whether or not a financially constrained but highly productive firm will benefit from group affiliation depends on its borrowing capacity vis-à-vis other affiliates.